Preparation of a poly(L-lactide-co -caprolactone) copolymer using a novel tin(II) alkoxide initiator and its fiber processing for potential use as an absorbable monofilament surgical suture - Ruengde S. (2017)
© 2016 Copyright Taylor & Francis Group, LLC. A poly(L-lactide-co-caprolactone) copolymer, P(LL-co-CL), of composition 75:25 mol% was synthesized via the bulk ring-opening copolymerization of L-lactide and ε-caprolactone using a novel bis[tin(II) monooctoate] diethylene glycol coordination-insertion initiator, OctSn-OCH2CH2OCH2CH2O-SnOct. The P(LL-co-CL) copolymer obtained was characterized by a combination of analytical techniques, namely nuclear magnetic resonance spectroscopy, gel permeation chromatography, dilute-solution viscometry, differential scanning calorimetry, and thermogravimetric analysis. For processing into a monofilament fiber, the copolymer was melt spun with minimal draw to give a largely amorphous and unoriented as-spun fiber. The fiber's oriented semicrystalline morphology, necessary to give the required balance of mechanical properties, was then developed via a sequence of controlled offline hot-drawing and annealing steps. Depending on the final draw ratio, the fibers obtained had tensile strengths in the region of 200-400 MPa.